2008
DOI: 10.1111/j.1349-7006.2008.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B has a potent antiproliferative effect on breast cancer cells in vitro and in vivo

Abstract: Cucurbitacins are a group of diverse triterpenoid substances isolated from plants with medicinal properties. One particularly potent family member is cucurbitacin B (CuB). The antiproliferative effects of CuB against human breast cancer cells were tested. Six human breast cancer cell lines were examined because they represent a diverse mix of breast cancer subtypes varying in expression of estrogen receptor (ER), Her2/neu, and p53 mutation. The antiproliferative effect of CuB were also studied in vivo. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 19 publications
8
84
1
1
Order By: Relevance
“…2A). These CSCC cells could recover to their normal morphology, if after 60 min of CuB exposure the cells were washed free of the drug and cultured for an additional 24 h. This is similar to morphologic changes noted in glioma, pancreatic and breast cancer cells (14,15,18). Our pulse-exposure experiments showed that a 24-h exposure to CuB (10 -7 M) largely inhibited growth of CSCC cells, while a shorter (2 or 9 h) exposure did not produce much growth inhibition.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…2A). These CSCC cells could recover to their normal morphology, if after 60 min of CuB exposure the cells were washed free of the drug and cultured for an additional 24 h. This is similar to morphologic changes noted in glioma, pancreatic and breast cancer cells (14,15,18). Our pulse-exposure experiments showed that a 24-h exposure to CuB (10 -7 M) largely inhibited growth of CSCC cells, while a shorter (2 or 9 h) exposure did not produce much growth inhibition.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies from our group demonstrated CuB can disrupt F-actins and microtubules in glioma, leukemia, as well as breast cancer cells (15,16,18). Given that the F-actin and the microtubule cytoskeleton is a key component involved in cell migration, we tested the ability of CuB to affect cell migration and found that CuB inhibited migration of CSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the antitumor activities of cucurbitacin B in various human cancer cell lines and tumor xenografts (49,50). However, the mechanisms underlying the anticancer activities are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Jayaprakasam and co-workers demonstrated the cytotoxic properties of cucurbitacins B, D, E and I, isolated from the fruits of Cucurbita andreana, against colon, breast, lung and central nervous system cancer cell lines (Jayaprakasam et al, 2003). Among this class of compounds, cucurbitacin B is the most studied, and while several studies demonstrated its efficacy in different models of cancer, including in vivo tumor xenografts (Liu et al, 2008;Wakimoto et al, 2008;Zhang et al, 2009;Chan et al, 2010), there is disagreement regarding the mechanisms underlying its anticancer activity. Suppression of the oncogene STAT 3 (signal transducer and activator of transcription 3) appears to be related to tumor inhibition (Zhang et al, 2004;Chan et al, 2010b), which does not exclude alternative mechanisms (Yasuda et al, 2010).…”
Section: Research Articlementioning
confidence: 99%